Multi-Resolution Modeling for Virtual Design - Cheng, Chiyi; Zhang, Mingmin; Pan, Zhigeng (International Journal of Virtual Reality, 2000)
The benefits of multi-resolution modeling techniques in virtual reality are vast, but one essential component of this model is how it can be used to speedup the process of virtual design and virtual prototyping. In this paper we propose a new multi-resolution representation scheme called MRM, which can support efficient extraction of both fixed and variable resolution modeling data for handling multiple objects in the same scene. One important feature of the MRM scheme is that it supports unified selective simplifications and selective refinements over the mesh representation of the object. In addition, multi-resolution models may be used to support real-time geometric transmission of data in collaborative virtual design and prototyping applications. These key features in MRM, may be applied to a variety of VR applications.